The Effect of Education Quality Mapping Toward Teacher Performance in Learning in Early Childhood Education Institutions - Istikomah, Eloh; Waluyo, Edi (Jurusan PGPAUD FIP UNNES, 2020)
The purpose of this study is to determine the Effect of Education Quality Mapping on Teacher Performance in Learning at Early Childhood Education Institutions in Brebes Regency. This research uses predictive quantitative methods. The population in this study is kindergarten teachers who are in Brebes Regency. The number of samples taken using cluster sampling techniques is 30 teachers who are in 8 kindergarten institutions in Brebes Regency. The data collection techniques used in this study use a scale that refers to the Likert scale. The assumption test is carried out using the normality test and linearity test. Hypothesis testing uses a simple linear regression test. The results of research on the Effects of Educational Quality Mapping on Teacher Performance in Learning at Early Childhood Education Institutions with a simple linear regression analysis showed an R Square value of 68.7%. This shows that the mapping of the quality of education has an influence on teacher performance in learning at early childhood education institutions. This shows that the better the mapping of the quality of education, the better the level of teacher performance in learning. Education quality mapping is contributed to the performance of teachers in learning at early childhood educational institutions by 68.7% and the remaining 31.3% is influenced by other factors not covered in this study.